CUETO CABALLERO. Marcos. Intellectual Thought and Aristocracy in San Márcos University: 1890-1920. Master of Arts,Department of History, Columbia University, New York,1983, 111. 57 p. - Hinojosa, Iván (1984)
No contiene resumen